Influence of different bench throw tempos on the strength of the upper extremities - Stankovic, R.; Bubanj, S.; Herodek, K.; Bubanj, R.; Markovic, S.; Nejic, D. (Facta Universitatis: Series Physical Education and Sport, 2009)
Upward pressure from the bench, i.e. the bench press, is the test of pure strength of the upper extremities. It includes lifting and lowering, as large a weight as it is possible and it evolved at the beginning of the 1960's, in the USA. There are certain discordances, in the previous research, concerning the strength training method, which refer to the methods of exercise performance, ie. to single vs. multiple sets, optimal repetition range for increasing muscular strength and endurance, speed of movement during exercise and optimal training frequency. The focus of this research was on the speed of movement during practice. The first sub-sample exercised by using cadence with a 2/4 tempo, and the second sub-sample exercised by using cadence with a 4/4 tempo. As the differences of relative and absolute gains in the lifted amounts, at the initial and final measurements, between two subsamples existed, but were not significant, it seems more reasonable to suggest a slower bench throw tempo. A slower bench throw tempo, i.e. slower movement speed, implies a smaller consumption of energy.